ChemInform Abstract: Enantioselective Multicomponent Condensation Reactions of Phenols, Aldehydes, and Boronates Catalyzed by Chiral Biphenols. Issue 17 (April 2016) - Barbato, Keith S.; Luan, Yi; Ramella, Daniele; Panek, James S.; Schaus, Scott E.
Abstract: Conditions for the chemoselective formation of either chiral di‐ and triarylmethane products or chiral 2, 4‐diaryl chromans are developed.